Cockfighter - Hellman, Monte, 1932-; Oates, Warren, 1928-1982; Willeford, Charles Ray, 1919-1988.; Rio Pinto Productions; Artists Entertainment Complex (Firm); Cinetel Films ([Hollywood, CA] : Rio Pinto Productions : Artists Entertainment Complex, Inc., 1974)
Frank Mansfield has wanted to win the Cockfighter of the Year medal for ages. Frank never speaks. After shooting his mouth off one too many times then losing a champion rooster in a casual hotel room cockfight, he swore never to speak again until he's won that award... --
Based on the novel by Charles Willeford.
Warren Oates, Richard B. Shull, Harry Dean Stanton, Ed Begley, Jr., Laurie Bird, Troy Donahue, Warren Finnerty, Robert Earl Jones, Patricia Pearcy, Millie Perkins, Steve Railsback, Tom Spratley.
Cinematographer, Nestor Almendros; editor, Lewis Teague; music, Michael Franks.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 14, 2015)
Keywords: Cockfighting -- Drama; Outlaws -- Australia -- Drama; Feature films; Internet videos; Streaming video